(untitled) (American Journal of Pedagogical and Educational Research, 2023)
At the end of the 19th century, Western and Russian literature and art paid more attention to depicting the inner world of the human heart, the aspects of the psyche with all their contradictions and dramatic aspects. As a result, the method of psychological analysis began to be effectively used in literary science. World scientists such as E. Enneken, W. Wundt, I. Folkelt, E. Elster, E. Bertrand, E. Grosse, A. A. Potebnya, D. N. Ovsyaniko-Kulikovsky scientifically and theoretically defined the role and importance of mental analysis in literary studies. justified.